Answer:
you answered it
Step-by-step explanation:
you put no blah blah blah
Answer:
La fórmula para el área total de superficie de un cono recto es T. S. A. = π rl + π r 2 . Ejemplo 2: Encuentre el área lateral de superficie de un cono recto si el radio es de 6 pulgadas y la altura de inclinación es de 10 pulgadas.
<span>Let's say e=a^2−b^2 and take each affirmation:
a. </span><span>both coefficients are perfect squares.
</span><span>a could be equal to 2 which is not a perfect square
b. </span><span>there are only two terms - obviously yes
</span><span>
c. </span>both terms have negative coefficients - as we can see just b has a negative <span>coefficient
Final answer b. </span><span>there are only two terms.</span>
<span>
</span>
Answer:
![Sum = (k+1)(k+2)](https://tex.z-dn.net/?f=Sum%20%3D%20%28k%2B1%29%28k%2B2%29)
Step-by-step explanation:
Given
k + 1 even numbers
Required
Their sum
This question will be solved using the sum of nth term of an AP
![S_n = \frac{n}{2}(2a + (n - 1)d)](https://tex.z-dn.net/?f=S_n%20%3D%20%5Cfrac%7Bn%7D%7B2%7D%282a%20%2B%20%28n%20-%201%29d%29)
Where
a = the first even number
![a = 2](https://tex.z-dn.net/?f=a%20%3D%202)
n = number of terms
![n =k +1](https://tex.z-dn.net/?f=n%20%3Dk%20%2B1)
d = difference between consecutive even numbers
![d = 2](https://tex.z-dn.net/?f=d%20%3D%202)
So, the expression becomes:
![Sum = \frac{k+1}{2}(2 * 2 + (k + 1 - 1) * 2)](https://tex.z-dn.net/?f=Sum%20%3D%20%5Cfrac%7Bk%2B1%7D%7B2%7D%282%20%2A%202%20%2B%20%28k%20%2B%201%20-%201%29%20%2A%202%29)
![Sum = \frac{k+1}{2}(2 * 2 + (k) * 2)](https://tex.z-dn.net/?f=Sum%20%3D%20%5Cfrac%7Bk%2B1%7D%7B2%7D%282%20%2A%202%20%2B%20%28k%29%20%2A%202%29)
![Sum = \frac{k+1}{2}(4 + 2k)](https://tex.z-dn.net/?f=Sum%20%3D%20%5Cfrac%7Bk%2B1%7D%7B2%7D%284%20%2B%202k%29)
![Sum = \frac{(k+1)(4 + 2k)}{2}](https://tex.z-dn.net/?f=Sum%20%3D%20%5Cfrac%7B%28k%2B1%29%284%20%2B%202k%29%7D%7B2%7D)
Factorize 4 + 2k
![Sum = \frac{(k+1)*2*(2 + k)}{2}](https://tex.z-dn.net/?f=Sum%20%3D%20%5Cfrac%7B%28k%2B1%29%2A2%2A%282%20%2B%20k%29%7D%7B2%7D)
![Sum = (k+1)*(2 + k)](https://tex.z-dn.net/?f=Sum%20%3D%20%28k%2B1%29%2A%282%20%2B%20k%29)
![Sum = (k+1)*(k+2)](https://tex.z-dn.net/?f=Sum%20%3D%20%28k%2B1%29%2A%28k%2B2%29)
![Sum = (k+1)(k+2)](https://tex.z-dn.net/?f=Sum%20%3D%20%28k%2B1%29%28k%2B2%29)
X+y = 46 so x = 46 - y
x-y = 4
substitute x = 46 - y into x-y = 4
x-y = 4
46 - y -y = 4
2y = 42
y = 21
x - y = 4
x - 21 = 4
x = 25
answer
the numbers are 21 and 25
double check
25 + 21 = 46
25 - 21 = 4